Laser phase noise tolerance in direct detection optical OFDM transmission using laser linewidth emulator - Ali, Younus Nidham; Zan, Zuraidah (Institute of Electrical and Electronics Engineers, 2017)
Laser phase noise tolerance in direct detection optical orthogonal frequency division multiplexing (OFDM) transmission system is experimentally demonstrated using laser linewidth emulator. With this linewidth emulator, the linewidth of the laser can be broadened independently without inducing other laser's noise characteristics such as relative intensity noise and chirping. The results show the effect of phase-to-intensity noise conversion due to the laser's phase noise and chromatic dispersion. This induces noise pedestals not only onto the optical carrier, but also to each of the subcarriers, and thus produces intersubcarriers interference. Measurements show 6 dB Q-degradation is suffered by the system when 10 MHz linewidth is used as compared to using narrowest emulator linewidth of 256 kHz. Transmission with the linewidth emulator set to 20 MHz is also shown where it can still be tolerated by 400 km of fiber at the Q of 9.606 dB with respect to $1.6\,× \,10^{{\rm - 3}}$ bit error rate. Simulation of 16 quadratic-amplitude modulation (QAM) (∼128 Gb/s) and 4 QAM (∼100 Gb/s) using VPItransmissionMaker are also presented to demonstrate the effect of carrier's phase-to-intensity noise conversion when a high data rate and wide OFDM signal bandwidth are used with the linewidth emulator as the system's laser source. The results show that a phase rotation term is insignificant for lower M -size QAM with fiber length less than 500 km. This presents the high effectiveness and reliability of the laser linewidth emulator to discretely determine an independent phase noise tolerance from the other laser's noise characteristics in the optical OFDM transmission system.